Multidetector Computed Tomography Versus Staging Laparoscopy for the Detection of Peritoneal Metastases in Esophagogastric Junctional and Gastric Cancer. Issue 5 (October 2017) - Leeman, Matthew F.; Patel, Dilip; Anderson, Judith; O'Neill, J. Robert; Paterson-Brown, Simon
Abstract : Objective: Staging laparoscopy (SL) is the gold standard investigation for detecting peritoneal metastases (PM) in patients with esophagogastric cancer but computed tomography (CT) has undergone significant improvements in recent years. The aim of this study was to investigate whether CT can replace SL in the detection of PM. Materials and Methods: Patients undergoing SL between January 2008 and December 2009 were identified from a prospectively collected database, operation notes were reviewed for the detection of PM. Corresponding CTs were reassessed by 2 experienced gastrointestinal radiologists, blinded to the SL results. Results: In total, 74 patients undergoing SL were included. Sensitivity and specificity of SL for PM were 94.1% (95% confidence interval, 69.2-99.7) and 100% (90.7-100). Sensitivity and specificity of CT were 58.8% (33.5-80.6) and 89.6% (76.6-96.1), respectively. Area under the curve of receiver operating characteristic curves for SL and CT were 0.971 (SE, 0.033) and 0.742 (SE, 0.78), respectively. Conclusions: CT cannot replace SL for the detection of PM in lower esophageal and gastric cancer.